Spivaks Strategic Essentialism Reading on Amy Tans The Red Candle - Vania Williany; Didimus E. Turuk (Indonesian Journal of English Language Studies (IJELS), 2019)
This paper analyzes the struggle of a Chinese-American woman in The Red Candle, one of the vignettes in Amy Tans novel The Joy Luck Club (1989). The main character namely Lindo Jong, is confined with patriarchy and tradition and is forced to marry her fiance at her teenage. Fascinatingly, Lindo can free herself from the arranged marriage and her oppressive new family by a clever scheme. Spivaks strategic essentialism is then applied to scrutinize this particular issue. Indeed, by strategic essentialism, Lindo still upholds her value as a Chinese woman and her respect to her filial piety, also, she can obtain her own independence as a woman.Keywords: Chinese-American woman, patriarchy, tradition, strategic essentialism